TikTok as an Informal Music Learning Platform: An Analysis of the Impact of Music Extracurricular Activities on Students of SMK 1 Pancasila Ambulu, Indonesia - Wiratmoko, Condro; Mahmud Ali Zain; Luluk Farida; Shuting Wu (Universitas Negeri Surabaya, 2025)
The TikTok phenomenon, which initially served solely as a source of entertainment, like other social media, has now evolved into a creative and educational medium for music learning. This study aims to explore TikTok’s role, focusing on SMK 1 Pancasila Ambulu Jember. Students take turns singing on TikTok, videos of which have circulated widely and been appreciated by the community. This study used a qualitative and visual ethnographic approach, supported by in-depth interviews involving students and teachers. The results indicate that activities on TikTok not only serve as a fun form of musical expression but also generate several more significant impacts beyond music. Through the viral power of the For You Page (FYP), several students have received scholarships to study abroad. Furthermore, this activity can enhance the school’s branding and reputation, both regionally and nationally. Furthermore, singing on TikTok strengthens students self-confidence and collective pride. This research provides a clear picture of TikTok’s potential for the future if utilized appropriately. Not only is it an innovative medium for artistic and social learning, but TikTok will go far beyond its typical use as a social media platform. These findings also highlight the need for teachers and schools to integrate digital technologies, to expand student learning outcomes and foster the critical and imaginative thinking needed. This study contributes to the literature on social media in music education by demonstrating how TikTok can function as an effective informal learning platform in the Indonesian context.